The complex I subunit NDUFA10 selectively rescues Drosophila pink1 mutants through a mechanism independent of mitophagy. - Joe H Pogson; Rachael M Ivatt; Alvaro Sanchez-Martinez; Roberta Tufi; Emma Wilson; Heather Mortiboys; Alexander J Whitworth (PLoS Genetics)
Mutations in PINK1, a mitochondrially targeted serine/threonine kinase, cause autosomal recessive Parkinson's disease (PD). Substantial evidence indicates that PINK1 acts with another PD gene, parkin, to regulate mitochondrial morphology and mitophagy. However, loss of PINK1 also causes complex I (CI) deficiency, and has recently been suggested to regulate CI through phosphorylation of NDUFA10/ND42 subunit. To further explore the mechanisms by which PINK1 and Parkin influence mitochondrial integrity, we conducted a screen in Drosophila cells for genes that either phenocopy or suppress mitochondrial hyperfusion caused by pink1 RNAi. Among the genes recovered from this screen was ND42. In Drosophila pink1 mutants, transgenic overexpression of ND42 or its co-chaperone sicily was sufficient to restore CI activity and partially rescue several phenotypes including flight and climbing deficits and mitochondrial disruption in flight muscles. Here, the restoration of CI activity and partial rescue of locomotion does not appear to have a specific requirement for phosphorylation of ND42 at Ser-250. In contrast to pink1 mutants, overexpression of ND42 or sicily failed to rescue any Drosophila parkin mutant phenotypes. We also find that knockdown of the human homologue, NDUFA10, only minimally affecting CCCP-induced mitophagy, and overexpression of NDUFA10 fails to restore Parkin mitochondrial-translocation upon PINK1 loss. These results indicate that the in vivo rescue is due to restoring CI activity rather than promoting mitophagy. Our findings support the emerging view that PINK1 plays a role in regulating CI activity separate from its role with Parkin in mitophagy.